Wood dust exposure and risks of nasopharyngeal carcinoma: a meta-analysis. (17th January 2020) - E, Meng; Yin, Jinzhu; Jin, Wu; Mao, Yiyang; Wu, Qihong; Qiu, Jun
Abstract: Background: Wood dust has been confirmed as one kind of human carcinogen. However, there are inconsistent study results of exploring the relationship of exposure to wood dust and occurrence of nasopharyngeal cancer (NPC). For a greater clarification, the authors systemically reviewed the relevant published articles on the relationship of exposure to wood dust and occurrence of NPC. And meta-analysis was conducted. Methods: The databases of PubMed, U.S. National Library of Medicine (MEDLINE), Embase and Science Direct were searched for the relevant publications. And Newcastle-Ottawa scale was employed for judging the quality of articles. Random-effect model was utilized for meta-analysis. Results: Among a total of 583 retrieved items, 10 case–control studies and 1 cohort study were selected. The ratio of maximal/minimal exposure concentration of wood dust yielded a pooled odd ratio (OR) of 2.18 (95% CI = 1.62–2.93, P = 0.063) with a moderate heterogeneity ( I 2 : 43.0%; P = 0.001). And subgroup analysis was performed for such factors as exposure status, exposure population and geographic region. No publishing bias was noted. Exposing to a high concentration of wood dust was positively proportional to occurring risk of NPC. Conclusion: It hints at the contributing effect of wood dust upon NPC. For eliminating the effects of other confounding factors, larger prospective cohort studies are required for further elucidating the relationship of exposure to wood dust and occurrence of NPC.